Experimental studies on a novel thin flat heat pipe heat spreader. (25th January 2016) - Li, Ji; Lv, Lucang
Highlights: A thin flat heat pipe with novel wick structure was fabricated. Operation characteristics of the flat heat pipe were identified. High heat flux of 100 W/cm 2 was achieved for this 2 mm flat heat pipe. Gravity has very small impact on its thermal performance. Abstract: The thermal performance of a copper-water flat heat pipe (100 mm × 50 mm × 2 mm) composed of a novel wick structure with an inner thickness for working fluid less than 1 mm has been investigated. The wick structure was made of sintered hybrid copper fine powder with diameters ranging from 50 µm to 100 µm. The effects of heating input, tilt angle, and cooling temperature on flat heat pipe working performance were studied experimentally. Results showed that the proposed flat heat pipe could effectively dissipate 120 W (100 W/cm 2 ) in the horizontal orientation with a thermal resistance of 0.196 °C/W. Moreover, it has been demonstrated that under air natural convection condition, the performances of the novel flat heat pipe were higher than those of thin copper sheet, showing an effective thermal conductivity more than 4 times of copper.